Lymphocystis viral disease impacts the diversity and functional profiles of the skin microbiome in gilthead seabream - Xavier, Raquel; Pérez-Losada, Marcos; Silva, Sofia Marques; Lino, Marilia; Faleiro, Maria João; Canada, Paula (Frontiers in Microbiology, 2024)
Lymphocystis viral disease (LVD) is a highly transmissible disease known to affect multiple fishes worldwide. Although this disease is usually benign, mortalities can occur in cases where infection is severe or secondary infection with bacterial pathogens and parasites occur. However, little is known about the bacterial dynamics of fish with LVD or what bacterial pathogens may be responsible for secondary infections. Here we assessed the effects of LVD on the skin microbiome of gilthead seabream by comparing 30 symptomatic, asymptomatic and recovered (three weeks after infection) fish using 16S rRNA high-throughput sequencing. Our results show that LVD is associated with significant changes in microbiome structure and function. Importantly, fish pathogens like Tenacibaculum maritimum and some Vibrio species increased their abundance. Moreover, microbial metabolic activities of the commensal microbiota that may confer some protection to fish were suppressed in diseased fish. After reducing fish cage density to treat symptoms and three weeks of recovery, the abundance of pathogens was significantly reduced and microbiome functionality was recovered, although community structure remained significantly different. These results show that LVD can severely disrupt the bacterial communities of the skin of the gilthead seabream, leading to an increase in bacterial pathogens responsible for relevant diseases in gilthead seabream farms.